Determining the Forage Importance Value of Mazar Al Chikh Ali forest and its possibility for grazing - شيخ محمد ياسين (Latakia University Journal -Biological Sciences Series, 2021)
This research had been implemented in Mazar Al Chikh Ali forest in Latakia Province. The Field surveys had been carried out in the mid - April 2021. There were 76 plant species recorded, wich were distributed in 68 genus and 31 families. The number of plant species, present in all investigated samples, was 40 species. The most common family was Poaceae With 16 species. In Second place was Fabaceae wirh 13 species and Asteraceae with only 7 species. Orysopsis holciformis (M.B.) Hach. obtained the highest values of relative importance in all investigated samples (6.55% in 1st , 6.42% in 2sd and 6.48% in 3th.). Species with forage significance were 55. It means 72.37%. Results showed that ΣRIV were 82.44% on the first site, 74.83% on the second site, 78.38% on the third site and the average for the three sites was 78.55%. Therefor we can conclude that the study area is generally suitable for grazing and that the area has a good forage importance.